2013
DOI: 10.1016/j.molcel.2013.01.015
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclic Mechanical Reinforcement of Integrin–Ligand Interactions

Abstract: Summary Cells regulate adhesion in response to internally-generated and externally-applied forces. Integrins connect the extracellular matrix to the cytoskeleton and provide cells with mechanical anchorages and signaling platforms. Here we show that cyclic forces applied to a fibronectin–integrin α5β1 bond switch the bond from a short-lived state with 1-s lifetime to a long-lived state with 100-s lifetime. We term this phenomenon “cyclic mechanical reinforcement” as the bond strength remembers the history of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
146
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(158 citation statements)
references
References 31 publications
11
146
0
1
Order By: Relevance
“…Upon ligand binding, integrins such as a5b1 form catch bonds whose conversion to a high-affinity state is stabilised by force [56] and whose bond strength 'remembers' force from previous applications [57]. This characteristic facilitates efficient and sustained mechanotransmission.…”
Section: Reviewmentioning
confidence: 99%
“…Upon ligand binding, integrins such as a5b1 form catch bonds whose conversion to a high-affinity state is stabilised by force [56] and whose bond strength 'remembers' force from previous applications [57]. This characteristic facilitates efficient and sustained mechanotransmission.…”
Section: Reviewmentioning
confidence: 99%
“…Beyond this critical force, the bond behaves as a slip bond, with lifetime decreasing with force [21,22], Here we are interested whether FAs would manifest the similar behavior upon cyclic stretch if FAs are mainly comprised of a cluster of slip bonds instead. What's more, a recent study suggested that the bond formed between y.5/S\ integrin and its ligand would shortly switch to a single state upon several cycles of periodical loading [24], after which the bond lifetime versus force may follow the Bell's law [25] that is for a slip bond.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that talin 1 is critical to the strength of this slip bond, suggesting that talin 1 is responsible for initiating this molecular slip bond between closely packed FN-integrin complexes [24]. Kong et al used AFM and membrane force probes to demonstrate that cyclic application of 5-25 pN forces to FN-integrin a 5 b 1 bond significantly increases bond lifetime and identified a mechanism for cell adhesion strengthening by the application of cyclic forces [25]. Furthermore, they demonstrated with AFM that increasing applied force between 10 and 30 pN prolongs integrin a 5 b 1 -FN fragment bond lifetime, demonstrating catch bond behavior [26].…”
Section: Adhesion Strength Quantificationmentioning
confidence: 99%